Efeito da inibição de receptores dopaminérgicos centraissobre os mecanismos termorregulatórios e fadiga em ratos - Roberta Maria Miranda (2009)
The present study investigated the effects of central dopamine on thermoregulatory mechanisms and performance of untrained rats submitted to submaximal exercise until fatigue with the blockage of the dopaminergic receptors D1 or D2. Male Wistar rats, 11-12 weeks-old, had the core temperature sensor in the abdominal cavity and the cronic canulla in the Right Cerebral Lateral Ventricle (VLD) were implanted under anesthesia. After adapting to the treadmill, rats were treated with a 2 ìL injection in the VLD of either saline solution (n= 6), SCH 23390 (SCH, 5x10-3 M), D1 antagonist, (n= 6) or eticlopride (ETI, 5x10-3 M), D2 antagonist, (n= 6). Imediatelly after the i.c.v. injection rats were submitted to a continuous exercise protocol until fatigue on the treadmill (v= 18 m·min-1, 5% grade, ~66% VO2max). Only the animals treated with SCHshowed reduction on exercise time to fatigue (TTE). However, the groups differed in the beginning of heat loss: the control group started after 30%, the ETI group after 50% and the SCH after 70% of TTE, demonstrating an impairment in heat loss with the inhibition of the dopaminergic receptors. This greater delay on tale vasodilation, evidenced in the SCH group, contributed to the increase of the heat storage rate and consequentdecrease on the animals performance in this group. The results show the involvement of central dopamine in continues exercise performance and thermoregulatory responses.